X=(x+0)(x+0)(x+-9)(x+8)(x+-2)(x+2)(x+-2)(x+2)

Simple and best practice solution for X=(x+0)(x+0)(x+-9)(x+8)(x+-2)(x+2)(x+-2)(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X=(x+0)(x+0)(x+-9)(x+8)(x+-2)(x+2)(x+-2)(x+2) equation:


Simplifying
X = (x + 0)(x + 0)(x + -9)(x + 8)(x + -2)(x + 2)(x + -2)(x + 2)

Reorder the terms:
X = (0 + x)(x + 0)(x + -9)(x + 8)(x + -2)(x + 2)(x + -2)(x + 2)
Remove the zero:
X = (x)(x + 0)(x + -9)(x + 8)(x + -2)(x + 2)(x + -2)(x + 2)

Reorder the terms:
X = x(0 + x)(x + -9)(x + 8)(x + -2)(x + 2)(x + -2)(x + 2)
Remove the zero:
X = x(x)(x + -9)(x + 8)(x + -2)(x + 2)(x + -2)(x + 2)

Reorder the terms:
X = x * x(-9 + x)(x + 8)(x + -2)(x + 2)(x + -2)(x + 2)

Reorder the terms:
X = x * x(-9 + x)(8 + x)(x + -2)(x + 2)(x + -2)(x + 2)

Reorder the terms:
X = x * x(-9 + x)(8 + x)(-2 + x)(x + 2)(x + -2)(x + 2)

Reorder the terms:
X = x * x(-9 + x)(8 + x)(-2 + x)(2 + x)(x + -2)(x + 2)

Reorder the terms:
X = x * x(-9 + x)(8 + x)(-2 + x)(2 + x)(-2 + x)(x + 2)

Reorder the terms:
X = x * x(-9 + x)(8 + x)(-2 + x)(2 + x)(-2 + x)(2 + x)

Multiply x * x
X = x2(-9 + x)(8 + x)(-2 + x)(2 + x)(-2 + x)(2 + x)

Multiply (-9 + x) * (8 + x)
X = x2(-9(8 + x) + x(8 + x))(-2 + x)(2 + x)(-2 + x)(2 + x)
X = x2((8 * -9 + x * -9) + x(8 + x))(-2 + x)(2 + x)(-2 + x)(2 + x)
X = x2((-72 + -9x) + x(8 + x))(-2 + x)(2 + x)(-2 + x)(2 + x)
X = x2(-72 + -9x + (8 * x + x * x))(-2 + x)(2 + x)(-2 + x)(2 + x)
X = x2(-72 + -9x + (8x + x2))(-2 + x)(2 + x)(-2 + x)(2 + x)

Combine like terms: -9x + 8x = -1x
X = x2(-72 + -1x + x2)(-2 + x)(2 + x)(-2 + x)(2 + x)

Multiply (-72 + -1x + x2) * (-2 + x)
X = x2(-72(-2 + x) + -1x * (-2 + x) + x2(-2 + x))(2 + x)(-2 + x)(2 + x)
X = x2((-2 * -72 + x * -72) + -1x * (-2 + x) + x2(-2 + x))(2 + x)(-2 + x)(2 + x)
X = x2((144 + -72x) + -1x * (-2 + x) + x2(-2 + x))(2 + x)(-2 + x)(2 + x)
X = x2(144 + -72x + (-2 * -1x + x * -1x) + x2(-2 + x))(2 + x)(-2 + x)(2 + x)
X = x2(144 + -72x + (2x + -1x2) + x2(-2 + x))(2 + x)(-2 + x)(2 + x)
X = x2(144 + -72x + 2x + -1x2 + (-2 * x2 + x * x2))(2 + x)(-2 + x)(2 + x)
X = x2(144 + -72x + 2x + -1x2 + (-2x2 + x3))(2 + x)(-2 + x)(2 + x)

Combine like terms: -72x + 2x = -70x
X = x2(144 + -70x + -1x2 + -2x2 + x3)(2 + x)(-2 + x)(2 + x)

Combine like terms: -1x2 + -2x2 = -3x2
X = x2(144 + -70x + -3x2 + x3)(2 + x)(-2 + x)(2 + x)

Multiply (144 + -70x + -3x2 + x3) * (2 + x)
X = x2(144(2 + x) + -70x * (2 + x) + -3x2 * (2 + x) + x3(2 + x))(-2 + x)(2 + x)
X = x2((2 * 144 + x * 144) + -70x * (2 + x) + -3x2 * (2 + x) + x3(2 + x))(-2 + x)(2 + x)
X = x2((288 + 144x) + -70x * (2 + x) + -3x2 * (2 + x) + x3(2 + x))(-2 + x)(2 + x)
X = x2(288 + 144x + (2 * -70x + x * -70x) + -3x2 * (2 + x) + x3(2 + x))(-2 + x)(2 + x)
X = x2(288 + 144x + (-140x + -70x2) + -3x2 * (2 + x) + x3(2 + x))(-2 + x)(2 + x)
X = x2(288 + 144x + -140x + -70x2 + (2 * -3x2 + x * -3x2) + x3(2 + x))(-2 + x)(2 + x)
X = x2(288 + 144x + -140x + -70x2 + (-6x2 + -3x3) + x3(2 + x))(-2 + x)(2 + x)
X = x2(288 + 144x + -140x + -70x2 + -6x2 + -3x3 + (2 * x3 + x * x3))(-2 + x)(2 + x)
X = x2(288 + 144x + -140x + -70x2 + -6x2 + -3x3 + (2x3 + x4))(-2 + x)(2 + x)

Combine like terms: 144x + -140x = 4x
X = x2(288 + 4x + -70x2 + -6x2 + -3x3 + 2x3 + x4)(-2 + x)(2 + x)

Combine like terms: -70x2 + -6x2 = -76x2
X = x2(288 + 4x + -76x2 + -3x3 + 2x3 + x4)(-2 + x)(2 + x)

Combine like terms: -3x3 + 2x3 = -1x3
X = x2(288 + 4x + -76x2 + -1x3 + x4)(-2 + x)(2 + x)

Multiply (288 + 4x + -76x2 + -1x3 + x4) * (-2 + x)
X = x2(288(-2 + x) + 4x * (-2 + x) + -76x2 * (-2 + x) + -1x3 * (-2 + x) + x4(-2 + x))(2 + x)
X = x2((-2 * 288 + x * 288) + 4x * (-2 + x) + -76x2 * (-2 + x) + -1x3 * (-2 + x) + x4(-2 + x))(2 + x)
X = x2((-576 + 288x) + 4x * (-2 + x) + -76x2 * (-2 + x) + -1x3 * (-2 + x) + x4(-2 + x))(2 + x)
X = x2(-576 + 288x + (-2 * 4x + x * 4x) + -76x2 * (-2 + x) + -1x3 * (-2 + x) + x4(-2 + x))(2 + x)
X = x2(-576 + 288x + (-8x + 4x2) + -76x2 * (-2 + x) + -1x3 * (-2 + x) + x4(-2 + x))(2 + x)
X = x2(-576 + 288x + -8x + 4x2 + (-2 * -76x2 + x * -76x2) + -1x3 * (-2 + x) + x4(-2 + x))(2 + x)
X = x2(-576 + 288x + -8x + 4x2 + (152x2 + -76x3) + -1x3 * (-2 + x) + x4(-2 + x))(2 + x)
X = x2(-576 + 288x + -8x + 4x2 + 152x2 + -76x3 + (-2 * -1x3 + x * -1x3) + x4(-2 + x))(2 + x)
X = x2(-576 + 288x + -8x + 4x2 + 152x2 + -76x3 + (2x3 + -1x4) + x4(-2 + x))(2 + x)
X = x2(-576 + 288x + -8x + 4x2 + 152x2 + -76x3 + 2x3 + -1x4 + (-2 * x4 + x * x4))(2 + x)
X = x2(-576 + 288x + -8x + 4x2 + 152x2 + -76x3 + 2x3 + -1x4 + (-2x4 + x5))(2 + x)

Combine like terms: 288x + -8x = 280x
X = x2(-576 + 280x + 4x2 + 152x2 + -76x3 + 2x3 + -1x4 + -2x4 + x5)(2 + x)

Combine like terms: 4x2 + 152x2 = 156x2
X = x2(-576 + 280x + 156x2 + -76x3 + 2x3 + -1x4 + -2x4 + x5)(2 + x)

Combine like terms: -76x3 + 2x3 = -74x3
X = x2(-576 + 280x + 156x2 + -74x3 + -1x4 + -2x4 + x5)(2 + x)

Combine like terms: -1x4 + -2x4 = -3x4
X = x2(-576 + 280x + 156x2 + -74x3 + -3x4 + x5)(2 + x)

Multiply (-576 + 280x + 156x2 + -74x3 + -3x4 + x5) * (2 + x)
X = x2(-576(2 + x) + 280x * (2 + x) + 156x2 * (2 + x) + -74x3 * (2 + x) + -3x4 * (2 + x) + x5(2 + x))
X = x2((2 * -576 + x * -576) + 280x * (2 + x) + 156x2 * (2 + x) + -74x3 * (2 + x) + -3x4 * (2 + x) + x5(2 + x))
X = x2((-1152 + -576x) + 280x * (2 + x) + 156x2 * (2 + x) + -74x3 * (2 + x) + -3x4 * (2 + x) + x5(2 + x))
X = x2(-1152 + -576x + (2 * 280x + x * 280x) + 156x2 * (2 + x) + -74x3 * (2 + x) + -3x4 * (2 + x) + x5(2 + x))
X = x2(-1152 + -576x + (560x + 280x2) + 156x2 * (2 + x) + -74x3 * (2 + x) + -3x4 * (2 + x) + x5(2 + x))
X = x2(-1152 + -576x + 560x + 280x2 + (2 * 156x2 + x * 156x2) + -74x3 * (2 + x) + -3x4 * (2 + x) + x5(2 + x))
X = x2(-1152 + -576x + 560x + 280x2 + (312x2 + 156x3) + -74x3 * (2 + x) + -3x4 * (2 + x) + x5(2 + x))
X = x2(-1152 + -576x + 560x + 280x2 + 312x2 + 156x3 + (2 * -74x3 + x * -74x3) + -3x4 * (2 + x) + x5(2 + x))
X = x2(-1152 + -576x + 560x + 280x2 + 312x2 + 156x3 + (-148x3 + -74x4) + -3x4 * (2 + x) + x5(2 + x))
X = x2(-1152 + -576x + 560x + 280x2 + 312x2 + 156x3 + -148x3 + -74x4 + (2 * -3x4 + x * -3x4) + x5(2 + x))
X = x2(-1152 + -576x + 560x + 280x2 + 312x2 + 156x3 + -148x3 + -74x4 + (-6x4 + -3x5) + x5(2 + x))
X = x2(-1152 + -576x + 560x + 280x2 + 312x2 + 156x3 + -148x3 + -74x4 + -6x4 + -3x5 + (2 * x5 + x * x5))
X = x2(-1152 + -576x + 560x + 280x2 + 312x2 + 156x3 + -148x3 + -74x4 + -6x4 + -3x5 + (2x5 + x6))

Combine like terms: -576x + 560x = -16x
X = x2(-1152 + -16x + 280x2 + 312x2 + 156x3 + -148x3 + -74x4 + -6x4 + -3x5 + 2x5 + x6)

Combine like terms: 280x2 + 312x2 = 592x2
X = x2(-1152 + -16x + 592x2 + 156x3 + -148x3 + -74x4 + -6x4 + -3x5 + 2x5 + x6)

Combine like terms: 156x3 + -148x3 = 8x3
X = x2(-1152 + -16x + 592x2 + 8x3 + -74x4 + -6x4 + -3x5 + 2x5 + x6)

Combine like terms: -74x4 + -6x4 = -80x4
X = x2(-1152 + -16x + 592x2 + 8x3 + -80x4 + -3x5 + 2x5 + x6)

Combine like terms: -3x5 + 2x5 = -1x5
X = x2(-1152 + -16x + 592x2 + 8x3 + -80x4 + -1x5 + x6)
X = (-1152 * x2 + -16x * x2 + 592x2 * x2 + 8x3 * x2 + -80x4 * x2 + -1x5 * x2 + x6 * x2)
X = (-1152x2 + -16x3 + 592x4 + 8x5 + -80x6 + -1x7 + x8)

Solving
X = -1152x2 + -16x3 + 592x4 + 8x5 + -80x6 + -1x7 + x8

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Simplifying
X = -1152x2 + -16x3 + 592x4 + 8x5 + -80x6 + -1x7 + x8

See similar equations:

| 75-4x=7x+20 | | S(x)=(x-0)(x+0)(x-9)(x+8)(x-2)(x+2)(x-2)(x+2) | | 5y-9+y+33=6y+30-3y | | 3x+10x-(7x+5)= | | x^2+12x+32= | | 3x(4x-3)(x+3)= | | 75x^2+5x-10=0 | | 9x+(-6y)=12 | | 12x^2+20x= | | e^6x=2 | | b^2+2b-15=0 | | -x+6-5x=14-2x | | 10x=23 | | 5x^2-3x-2=0 | | 16(v+4)-4v=4(3v+3)-15 | | 2r^2+7r+5=0 | | x^4-27x^2+162=0 | | 25n-7=5n+3 | | .1x+.7y=5 | | 0.25(5b+11)=19 | | 100s^2-9=0 | | -54x^2-99x-15=0 | | 7x-5yi=-6i+24 | | 13x+8+8x=9x-22 | | 9y^3-49y=0 | | 10y^2+13y-2= | | 24x^2+26x+6=0 | | 12x=-2(x-16) | | 0.75(5b+11)=19 | | Y-5=0 | | 8x^2-14x-15=0 | | x^2+6x=91 |

Equations solver categories